Hubungan Indeks Massa Tubuh dan Posisi Kerja dengan Keluhan Muskuloskeletal pada Ibu Rumah Tangga di Desa Bedali - Fariska Anggun Cahya Rani; Elvareta Ilna Cahyani; Kurnia Fatma Hardini (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Musculoskeletal disorders (MSDs) are health problems involving joints, ligaments, muscles, and bones due to poor posture. A study showed that women, particularly housewives, have a higher prevalence of MSDs and suggested that household chores could be an independent risk factor for the increase in MSDs. This study aims to identify independent risk factors that may cause musculoskeletal complaints among housewives in Bedali, Ngancar. The research method uses a cross-sectional survey on 20 housewives aged 26 – 35 years, with data collected through interviews and the Nordic Body Map (NBM) questionnaires combined with demographic data. The Nordic Body Map (NBM) is a questionnaire used to detect discomfort or pain in the body and identify musculoskeletal disorders (MSDs) among workers. Data analysis used Spearman Correlation Coeficient test and Chi-Square tests. The results showed a strong correlation between Body Mass Index and working positions, specifically standing and squatting. Therefore, BMI and work positions, specifically standing and squatting can be independent risk factor for musculoskeletal complaint. Based on these findings, it is recommended that health promoters emphasizes educating the entire community about work safety, particulary regarding how to perform activities with ergonomic working positions. This study provides theoretical benefits for public health education.